POPULASI DAN PERSENTASE SERANGAN HAMA PENGGEREK BATANG (Ostrinia furnacalis Guenee) PADA TANAMAN JAGUNG MANIS (Zea mays saccharata Sturt) DI KECAMATAN TOMOHON UTARA KOTA TOMOHON - Sigit A. Pratama; James B. Kaligis; Jimmy Rimbing (Universitas Sam Ratulangi, 2015)
ABSTRACT In Indonesia, corn is the second important food crops after rice. Corn is also used as food, are also used as animal feed. Pests that attack sweet corn crop is pest O. furnacalis. This study aims to determine the percentage of the population and O. furnacalis pests on crops of sweet corn in North Tomohon Tomohon sub district were housed in three villages, namely Village Wailan, Kakaskasen and Kakaskasen III. The timing of the study for four months starting from the month of November 2014 to February 2015. This study uses survey research and data collection population and the percentage of larvae attack O. furnacalis. Each village determined the sweet corn crop plots measuring approximately 0,5 ha then divided by five sub plots scattered observations diagonally and taken as many as 40 plants. Larval population data retrieval is done on old plants 54 days after planting (dat), 61 dat, dat 68 and dat 75 with an interval of seven days. The results showed an average population of O. furnacalis found in sweet corn planting in the village Wailan is 9,35 individuals, followed by Village Kakaskasen 9,00 individuals and in the Village Kakaskasen III 6,85 individuals , The observation of the plants aged 54 to 75 dat O. furnacalis pest larvae attack sweet corn plants in North Tomohon sub district, but still relatively small percentage of attacks. The average percentage of attacks O. furnacalis highest in Sub Kakaskasen ie 11,12%, followed by Sub Wailan 8,50 % and 7,62% in Kakaskasen III. Keywords: Population, Percentage, O. furnacalis, Sweet Corn